İsa Mesih’in Tanrısallığının Taklidi ve Bunun Orta Çağ Hıristiyan Dünyasındaki Yansımaları Üzerine Bir Değerlendirme/An Evaluation of the Imitation of the Divinity of Jesus Christ and Its Reflections in Medieval Christianity - Zekiye Sönmez (Oksident, 2022)
Jesus Christ has been widely discussed in Christianity in terms of his identity, personality, and position, and this has led to the emergence of a branch of science called Christology. Jesus has been seen as different from others because of his birth, earthly actions, and death on the cross. Because of these differences, the subject that he is not a mere human being but can also be God has been one of the most preoccupying issues for Christians. In addition, Christians have discussed the issue of how to model or imitate him as a human or God. In this context, Paul, who is accepted as the founder of today’s Christianity, has been the initiator of the “Imitatio Christi” issue in Christianity with the words “As I imitate Christ, you also imitate me.” The imitation or follow-up of Christ has been a subject discussed in the Christian world since him. The article discusses the imitation of the divinity of Jesus Christ and its reflections in the medieval Christian world.